(untitled) - Watson, James D. (New York, 1983)
The new edition explores core concepts in molecular biology in a contemporary inquiry-based context, building its coverage around the most relevant and exciting examples of current research and landmark experiments that redefined our understanding of DNA. As a result, students learn how working scientists make real high-impact discoveries.
Keywords: Recombinant DNA